2008
DOI: 10.1021/nl080044m
|View full text |Cite
|
Sign up to set email alerts
|

Distance Dependent Spectral Tuning of Two Coupled Metal Nanoparticles

Abstract: The spectral properties of two spherical metallic nanoparticles of 80 nm in diameter are examined with regard to the interparticle distance and relative polarization of the excitation light. One Au nanoparticle is attached to a scanning fiber probe and the second to a scanning substrate. This configuration allows three-dimensional and arbitrary manipulation of both distance and relative orientation with respect to the incident light polarization. As supported by numerical simulations, a periodic modulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 28 publications
4
73
1
Order By: Relevance
“…More specifically, if we had not investigated the angle dependence (as, e.g., Ref. [7,8,10, and 11]), i.e., if we would have had only data points at k || = 0 for our discussion, our data were also compatible with the assumption of nearest-neighbor interaction only. In other words, the fact that we have measured simultaneously the dependence of the resonance frequency and of the damping on lattice constant as well as the dependence on angle of incidence (equivalent to in-plane wave vector) has provided a much more stringent test ground for a detailed understanding of split-ring-resonator arrays.…”
Section: Complete Numerical Calculationsmentioning
confidence: 79%
See 1 more Smart Citation
“…More specifically, if we had not investigated the angle dependence (as, e.g., Ref. [7,8,10, and 11]), i.e., if we would have had only data points at k || = 0 for our discussion, our data were also compatible with the assumption of nearest-neighbor interaction only. In other words, the fact that we have measured simultaneously the dependence of the resonance frequency and of the damping on lattice constant as well as the dependence on angle of incidence (equivalent to in-plane wave vector) has provided a much more stringent test ground for a detailed understanding of split-ring-resonator arrays.…”
Section: Complete Numerical Calculationsmentioning
confidence: 79%
“…Thus, a detailed understanding of the mechanisms determining this linewidth is highly desirable. It is well known by now that both near-field as well as far-field coupling effects significantly modify the resonance position and lineshape of the response of coupled metal nanoparticles [7][8][9][10] . Likewise, for SRR arrays the damping is not only determined by the properties of the individual SRRs but also by the mutual interaction of SRRs in a two-dimensional array 5,6,11 or in a three-dimensional crystal [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of such modes in plasmonic structures is extensively discussed in other reviews 28,29 . Further, the changes to the resonance position and width associated with mode--hybridisation depend strongly on the separation between the two particles 30,31 , due in part to the attenuation of the near--fields with distance 32,33 and in part due to interference arising because of retardation, i.e. the finite speed of light 30,31,34 .…”
Section: Box1: From Plasmonic Antennae To Meta--atomsmentioning
confidence: 99%
“…Theoretical and experimental reports have shown that at large interparticle distances, retardation effects induce a periodic modulation of the scattering cross-section for both longitudinally and transversely coupled particles [21]. Furthermore, experimental results obtained recently on particle pairs using an excitation in total internal reflection geometry showed that two efficiently scattering transverse modes can be observed [22] which is inconsistent with the hybridization model.…”
Section: Introductionmentioning
confidence: 96%